Genomic, transcriptomic, and metabolomic analyses reveal convergent evolution of oxime biosynthesis in Darwin’s orchid - Kai Jiang; Birger Lindberg Møller; Shaofan Luo; Yu Yang; David R. Nelson; Elizabeth Heather Jakobsen Neilson; Joachim Møller Christensen; Kai Hua; Chao Hu; Xinhua Zeng; Mohammed Saddik Motawie; Tao Wan; et al. (Molecular Plant, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Restoration of linear disturbances from oil-and-gas exploration in boreal landscapes: How can network models help? - Denys Yemshanov; Mackenzie Simpson; Ning Liu; Aaron Petty; Frank H. Koch; Eric Neilson; Cynthia Chand; George Duffy; Vita Hoyles; Chris Mallon (Journal of Environmental Management, 2023)

Conservation triage at the trailing edge of climate envelopes - Sophie L. Gilbert; Kate Broadley; Darcy Doran‐Myers; Amanda Droghini; Jessica A. Haines; Anni Hämäläinen; Clayton T. Lamb; Eric W. Neilson; Stan Boutin (Conservation Biology, 2020)

Quantifying fear effects on prey demography in nature - Michael J. L. Peers; Yasmine N. Majchrzak; Eric Neilson; Clayton T. Lamb; Anni Hämäläinen; Jessica A. Haines; Laura Garland; Darcy Doran‐Myers; Kate Broadley; Rudy Boonstra; Stan Boutin (Ecology, 2018)
In recent years, it has been argued that the effect of predator fear exacts a greater demographic toll on prey populations than the direct killing of prey. However, efforts to quantify the effects of fear have primarily relied on experiments that replace predators with predator cues. Interpretation of these experiments must consider two important caveats: (1) the magnitude of experimenter‐induced predator cues may not be realistically comparable to those of the prey's natural sensory environment, and (2) given functional predators are removed from the treatments, the fear effect is measured in the absence of any consumptive effects, a situation which never occurs in nature. We contend that demographic consequences of fear in natural populations may have been overestimated because the intensity of predator cues applied by experimenters in the majority of studies has been unnaturally high, in some instances rarely occurring in nature without consumption. Furthermore, the removal of consumption from the treatments creates the potential situation that individual prey in poor condition (those most likely to contribute strongly to the observed fear effects via starvation or reduced reproductive output) may have been consumed by predators in nature prior to the expression of fear effects, thus confounding consumptive and fear effects. Here, we describe an alternative treatment design that does not utilize predator cues, and in so doing, better quantifies the demographic effect of fear on wild populations. This treatment substitutes the traditional cue experiment where consumptive effects are eliminated and fear is simulated with a design where fear is removed and consumptive effects are simulated through the experimental removal of prey. Comparison to a natural population would give a more robust estimate of the effect of fear in the presence of consumption on the demographic variable of interest. This approach represents a critical advance in quantifying the mechanistic pathways through which predation structures ecological communities. Discussing the merits of both treatments will motivate researchers to go beyond simply describing the existence of fear effects and focus on testing their true magnitude in wild populations and natural communities.

The impact of tropospheric ozone on landscape-level merchantable biomass and ecosystem carbon in Canadian forests - Jean-Sébastien Landry; Eric T. Neilson; Werner A. Kurz; Kevin E. Percy (European Journal of Forest Research, 2013)

Future Spruce Budworm Outbreak May Create a Carbon Source in Eastern Canadian Forests - Caren C. Dymond; Eric T. Neilson; Graham Stinson; Kevin Porter; David A. MacLean; David R. Gray; Michel Campagna; Werner A. Kurz (Ecosystems, 2010)

Optimizing carbon sequestration in commercial forests by integrating carbon management objectives in wood supply modeling - Charles P.-A. Bourque; Eric T. Neilson; Chris Gruenwald; Samantha F. Perrin; Jason C. Hiltz; Yvon A. Blin; Geoffrey V. Horsman; Matthew S. Parker; Christie B. Thorburn; Michael M. Corey; Fan-rui Meng; D. Edwin Swift (Mitigation and Adaptation Strategies for Global Change, 2007)

Localization of the mouse kidney disease (kd) gene to a YAC/BAC contig on Chromosome 10 - Katherine MacRae Dell; Yi-Xun Li; Min Peng; Eric G. Neilson; David L. Gasser (Mammalian Genome, 2000)